Dawn rider - Miles, Terry; Slater, Christian; Hennessy, Jill, 1968-; Sutherland, Donald, 1935-; Clayton, George; Nasser Group North (Firm); Vivendi Entertainment (Firm) (Universal City, Calif. : distributed by Vivendi Entertainment, 2012)
When the father of gunslinger John Mason is killed by masked bandits, Mason sets out to find the killers. During his quest, he finds himself in a love triangle with Alice, the determined and beautiful woman also adored by John's best friend.
DVD, widescreen format ; Dolby digital ; NTSC 1.
Closed captioned.
Christian Slater, Jill Hennessy, Donald Sutherland, George Clayton.
Music, James Guttridge and Sean Hosein ; production designer, Brian Davie ; editor, Trevor Mirosh ; director of photography, Norm Li.
Originally broadcast on television in 2012.
Rated R, for violence and language.
Keywords: Shooters of firearms -- Drama; Revenge -- Drama; Triangles (Interpersonal relations) -- Drama; Western films; Film remakes; Video recordings for the hearing impaired